2007
DOI: 10.1029/2006ja011942
|View full text |Cite
|
Sign up to set email alerts
|

SERSIO: Svalbard EISCAT Rocket Study of Ion Outflows

Abstract: [1] The SERSIO sounding rocket was launched from Ny-Alesund, Svalbard, into a type 2 ion upflow event simultaneously observed by the European Incoherent Scatter (EISCAT) radar facility in Longyearbyen on 22 January 2004 at 0857 UT. It reached an apogee of 782 km. In situ wave data and thermal particle measurements in the cusp/cleft region clearly show core thermal ion temperature enhancements up to 0.8 eV in association with 0-4 kHz broadband extremely low frequency wave activity (BBELF). The in situ observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 45 publications
2
44
0
Order By: Relevance
“…We see both in this example, and in the dayside example of Frederick-Frost et al (2007) that soft electron precipitation appears as the trigger for this process. With the SIERRA data we can see the details of both the electron precipitation and the ion upflow, as well as an indirect observation of the higher altitude transverse ion acceleration process, through the ions which do not escape but precipitate back down past the payload.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We see both in this example, and in the dayside example of Frederick-Frost et al (2007) that soft electron precipitation appears as the trigger for this process. With the SIERRA data we can see the details of both the electron precipitation and the ion upflow, as well as an indirect observation of the higher altitude transverse ion acceleration process, through the ions which do not escape but precipitate back down past the payload.…”
Section: Discussionmentioning
confidence: 99%
“…The SCIFER and AMICIST Bonnell et al, 1996) experiments observed the low altitude signatures of broadband ELF (BBELF) transverse ion heating subsequently quantified by higher-altitude Freja (Andre et al, 1998;Knudsen et al, 1998a, b;Wahlund et al, 1998) and FAST observations (Lynch et al, 2002;Strangeway et al, 2005). This paper reporting SIERRA rocket observations on the nightside and Frederick-Frost et al (2007) reporting SERSIO rocket observations on the dayside both describe even lower altitude signatures: the initiation of ion heating and upflow that may seed wave particle interactions at higher altitudes.…”
Section: Science Background and Outlinementioning
confidence: 99%
See 1 more Smart Citation
“…detector [Frederick-Frost et al, 2007]. Figure 10 also illustrates the different widths of the field-aligned population which corresponds to the ionospheric electron temperature.…”
Section: Observationsmentioning
confidence: 99%
“…More recently, Lunde et al (2007) suggested that the electron precipitation energy flux, the characteristic energy and harder precipitation could be of importance in the process of generating NEIALs. Frederick-Frost et al (2007) suggest that NEIALs and Broad Band Extremely Low Frequency (BBELF, <5 kHz) waves are indicative of the same phenomenon, in which case the parametric decay of Langmuir waves is not a likely explanation.…”
Section: Introductionmentioning
confidence: 99%